LANDASAN TEORITIS PENGEMBANGAN NOVEL SEBAGAI MEDIA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) UNTUK MEMBENTUK KARAKTER ISLAMI - Anny Izzatul Mujahidah (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2025)
This article discusses the development of novels as an alternative learning medium in Islamic Religious Education (PAI) to shape Islamic character. Conventional memorization and normative learning approaches are considered ineffective in developing students' understanding of character and religiousness. Therefore, story-based media such as novels can be an innovation capable of conveying Islamic values ​​in a more touching, contextual, and reflective manner. This research uses a Research and Development (R&D) approach with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. This article presents a needs analysis and product development plan for a novel containing Islamic character education values. The results indicate that novels have great potential to increase learning interest, strengthen emotional engagement, and shape students' Islamic character more naturally.